Feed- based infectious bursal disease vaccination in village chicken - Alias, Muhamad Syafiq Aiman (2018)
Infectious bursal disease (IBD), also known as Gumboro disease, is an acute, highly contagious viral infection in chickens that can be exhibited by inflammation and followed by the atrophy of the bursa of Fabricius and immunosuppression. Clinically the disease can be seen only in chickens older than 3 weeks. Vaccination represents a very useful method for IBD controlling. The timing of optimal vaccination, doses used and the administration routes represent the most important factors in controlling the disease. In addition, the immunogenicity and histopathology of chickens can be used to monitor IBD in flocks. However, the studies between certain breed of chicken such as village chicken and IBD vaccine is lacking. The current research present an overview of immunogenicity and histopathology of UPM-bred village chickens vaccinated with IBD vaccine via feed. It was the objective of this study to evaluate and determine the most effective route for IBD vaccination on UPM-bred village chicken. In the experiment, one hundred and five day-old UPM-bred village chicks were reared in experimental house. The chicks were randomly divided into 3 groups which were; group A (feed based IBD vaccination), group B (IBD vaccination via intraocular route), and group C (control). The chickens in group A and B were vaccinated at day 14 with the IBD vaccine, administered according to the manufacturer's recommendations via feed and intraocular routes (0.1ml/chick). Five chicks in the control group were sacrificed at 1, 7, 14, 21, 28, 35 and 42 days of age. Five chickens each from the groups A and B were sacrificed at 21, 28, 35 and 42 days of age. Body weights were taken and serum samples were collected for IBD antibody detection using enzyme linked immunosorbent assays (ELISA) prior to necropsy. On necropsy, the gross lesions were recorded and the bursa of Fabricius was weighed and fixed in 10% buffered formalin for histopathological examination. The study proved that attenuated live strain IBD vaccine is safe and effective to be used. There were no clinical signs of IBD recorded throughout the trial in all groups of chickens. There were no significant (p>0.05) differences in body weight between the 3 groups. The bursa weight of the chickens in groups A and B were insignificantly (p>0.05) different but were significantly (p<0.05) lower than the control group at day 21 and above. At the end of the study, it is confirmed that feed based vaccination can induce the protective level of IBD antibody as high as the intraocular route. In addition, feed based IBD vaccination does not affect the weight of the village chickens significantly compared to the intraocular route vaccination.